Analysis of consumer habits and attitudes on the Hungarian beef and rabbit market - Szakály, Zoltán; Szigeti, Orsolya; Szente, Viktória (Applied Studies in Agribusiness and Commerce, 2009)
As a consortium partner the authors took part in a research project aiming at the development of high added value, healthy and environment friendly animal products. From among the products developed by the consortium (rabbit meat, omega3-fatty acid enriched beef, goose liver from non forcible feeding, selenium-, vitamin-E and natural color enriched eggs) the present study describes the results concerning beef and rabbit meat. The given products are chosen because they are produced in and exported from Hungary in considerable quantities and their competitiveness can be further improved. In order to able to map the consumer preferences a 300 count nationwide, representative, questionnaire based survey was designed and performed. Actual products were tested by focus groups and professional interviews. Beside the specific features of the products a common character is that the marketing strategy focuses on the distinctive nutritional benefits and other quality parameters that seem to be of crucial importance for the targeted consumer segment. Their unique character and health protecting effects make their branding and using community labeling easy. Their positioning points toward the prestige products therefore consumers tend to accept higher prices. In marketing communication the image building advertisement can be a common goal.